Risk of pacing-induced cardiomyopathy in patients with high-degree atrioventricular block – comparison between right ventricular pacing sites using computed tomography. (3rd October 2022) - Fruelund, P Z; Sommer, A M; Lundbye-Christensen, S; Zaremba, T; Soegaard, P; Graff, C; Vraa, S; Mahalingasivam, A A; Pedersen, M R; Riahi, S
Abstract: Background: Right ventricular (RV) pacing may induce significant left ventricular (LV) dyssynchrony resulting in pacing-induced cardiomyopathy (PICM). LV activation sequence is affected by RV pacing site and previous studies suggest that RV septal pacing may be superior compared to traditional RV apical pacing. However, results are conflicting and randomized controlled trials have failed to show clear benefits from RV septal pacing. Traditionally, studies have applied fluoroscopy to determine RV lead implantation site. However, locating pacing site using this method is known to be inaccurate and poorly reproducible compared with cardiac computed tomography (CT). The purpose of our study was to evaluate the association between RV pacing site determined by cardiac CT and risk of PICM. Methods: We retrospectively included 153 patients with pre-implant LV ejection fraction (LVEF) ≥50% who underwent fluoroscopy-guided dual chamber pacemaker implantation due to high-degree atrioventricular block between March 2012 and May 2020. All patients attended a follow-up visit including cardiac CT and transthoracic echocardiography. RV lead position was evaluated from CT dividing the RV into three segments: apical, septum or free wall (Figure 1). Furthermore, RV lead position estimated by the implanting physician, using fluoroscopy during pacemaker implantation, was retrieved from medical records. The primary endpoint was PICM defined as ≥10% decrease in LVEF from time of pacemaker implantation to follow-up, resulting in LVEF <50%. Results: Mean duration of follow-up was 3.7 years (range 2.1–8.7). The implanting physician estimated 131 (85.6%) leads to be located septal, 5 (3.3%) located non-septal and 17 (11.1%) were unknown. Based on CT, 48 (31.4%) leads were located septal and 105 (68.6%) were located non-septal of which 31 were located on the free wall (20.4%). With CT as the golden standard, 47 (35%) leads were estimated correctly during fluoroscopy-guided implantation. No significant differences between patient characteristics in the CT-estimated septal and non-septal groups were observed except for ischemic heart disease (P=0.05) (Table 1). There were 16 (33.3%) patients in the septal group who developed PICM compared to 31 (29.5%) in the non-septal group (P=0.6). Adjusting for ischemic heart disease did not change this result. In the septal group, the change in LVEF from baseline to follow-up was −9.0±10.4% compared to −7.5±9.1% in the non-septal group (P=0.4). Conclusion: In total 31% developed PICM despite having a normal pre-implant LVEF with no observed difference between RV septal and non-septal pacing. With CT as the golden standard, RV leads were inaccurately located during fluoroscopy-guided pacemaker implantation with only 35% being located correctly. Misclassification of pacing sites in previous studies may have contributed to the inconsistent results. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Svend Andersens FondKarl G Andersens Fond